Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan - Miskiani, Komang Alit; Bagia, I Wayan (Universitas Pendidikan Ganesha, 2020)
The research aimed to obtain an explanatory findings were tested on the effect of (1) work motivation and work discipline influencing employee performance, (2) work motivation influences work discipline, (3) work motivation influences employee performance, and (4) work discipline on employee performance. The subjects in this study were all employees of Koperasi Serba Usaha Tunas Mertha Mandirii Singaraja and the object of this research were work motivation, work discipline and employee performance. The population in this study were all employees of 39 people. This research includes population research because all employees are used as observation units. Data were collected by questionnaire method, then analyzed by path analysis. The findings of this study show that (1) work motivation and work discipline has a positive effect on employee performance, (2) work motivation has a positive effect on work discipline, (3) work motivation has a positive effect on employee performance, and (4) work discipline has a positive effect on the performance of Koperasi Serba Usaha Tunas Mertha Mandiri Singaraja.Â